Developmental fate of Rhizobium meliloti bacteroids in alfalfa nodules. - Paau, A S (1980)
Nitrogen-fixing bacteroids are degraded during nodule senescence. This is in contrast to recent implications that viable bacteroids can be released into soil from legume nodules. Rhizobia originating from persistent infection threads in senescing nodule plant cells seem to be the source of viable cells required for perpetuation of the Rhizobium spp. population in the soil. Our conclusions were derived from electron microscopic examination of stages of development and senescence of alfalfa root nodules.